Long-Read Sequencing Revealed an Extensive Transcript Complexity in Herpesviruses - Tombácz, Dóra; Balázs, Zsolt; Csabai, Zsolt; Snyder, Michael; Boldogkői, Zsolt (Frontiers in Genetics, 2018)
Long-read sequencing (LRS) techniques are very recent advancements, but they have already been used for transcriptome research in all of the three subfamilies of herpesviruses. These techniques have multiplied the number of known transcripts in each of the examined viruses. Meanwhile, they have revealed a so far hidden complexity of the herpesvirus transcriptome with the discovery of a large number of novel RNA molecules, including coding and non-coding RNAs, as well as transcript isoforms, and polycistronic RNAs. Additionally, LRS techniques have uncovered an intricate meshwork of transcriptional overlaps between adjacent and distally located genes. Here, we review the contribution of LRS to herpesvirus transcriptomics and present the complexity revealed by this technology, while also discussing the functional significance of this phenomenon.